The indissolubility of marriage & the Council of Trent - Brugger, E. Christian (Catholic University of America Press, 2017)
This important volume examines the Catholic Church's doctrine on the indissolubility of marriage as taught by the 16th century Ecumenical Council of Trent (1545-1563). In the Council's reply to Reformation challenges on the sacraments, it took up the question of whether anything-in particular, adultery-could dissolve a sacramental marriage. The question was discussed at length in 1547, and again, after a lengthy delay, in 1563. The considerations culminated in doctrinal definitions on marriage invested with the full authority of the Catholic Church. For historical reasons that the author considers in detail (reason related to the relationship between Rome and the Greek Orthodox churches), the most important of these definitions-Canon 7-was ambiguously worded. This has led to a centuries-long debate on the intentions of the council for the meaning of that canon, and, indeed for the council's wider teaching on martial indissolubility. E. Christian Brugger aims to shed light on this debate. The Indissolubility of Marriage and the Council of Trent begins by laying out the fundamental questions addressed by Trent, the ambiguities of Canon 7, and the nature of the interpretive debate that's been underway since the early seventeenth century. It examines the views on divorce and remarriage of Luther and Calvin as the council fathers would have known them, as well as the beliefs and practices of the Greek churches